Estudo comparativo da microbiota bacteriana cultivável associada à Anopheles darlingi Root, 1926, e seu hábitat - Rocha, Elerson Matos (2015)
Malaria is a disease responsible for thousands of deaths worldwide every year. The etiologic agents are protozoa of the genus Plasmodium that are transmitted by female Anopheles mosquitos, considered vector in these conditions. Despite several measures are employed to control malaria and also of many international control programs being implemented, with the focus always returned to mosquito vectors, which each decade exhibit marked resistance to conventional insecticides, the disease remains very common and It presents thousands of cases, a fact that leads to the search for new vector mosquito control methods. Research based on biological control using micro-organisms, are becoming alternatives for controlling these most frequent form of vectors. Little is known about microbial communities that live in symbiosis with the larvae of Anopheles. Know and understand the functions of the diversity of bacteria that live associated with the malaria vector, will allow to understand how the relationship between bacteria, insects and protozoa happen and extensive research may be used such information for future work in order to control this disease in the world. Molecular methodologies contribute to this development analysis of microbial diversity and can reveal a scenario of the distribution of bacteria in the natural habitat of larval breeding of the malaria vector. This study aimed to make a comparative analysis of cultivable bacterial groups associated with larvae and pupae of Anopheles darlingi and their habitat in the city of Coari and Manaus in Amazonas state. Sampling was carried out in the city of Coari and Manaus. Bacteria were inoculated and purified in selective media. DNA extractions were performed and the identification was carried out from the amplification and sequencing of the 16S rDNA fragment. In this study, 1,845 were isolated bacteria from the city of Coari and Manaus. They were identified from water samples, 3rd and 4th larval and pupal stages of A. darlingi, 46 different species of bacteria belonging to 23 genera phyla Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes. The species Bacillus sp., Chromobacterium sp., Chromobacterium violaceum, Bacillus thuringiensis and Pseudomonas sp had the highest percentage of isolates obtained. It was obtained a collection that makes the first step towards a promising control study involving malaria bacteria associated with A. darlingi and their habitat in the Brazilian Amazon region. The next step will be to use the isolates identified in this study work aimed at understanding the relationship of bacteria with the malaria parasite in the midgut of the mosquito A. darlingi. Keywords: Bacterial microbiota - Anopheles darlingi - Malaria - Amazon.